Indonesia’s COVID-19 Trend After the End of a Public Health Emergency of International Concern: Preparation for an Endemic - Novarisa, Nessa; Helda, Helda; Mulyadi, Rahmad (UI Scholars Hub, 2023)
Three years into the pandemic, the World Health Organization revoked the COVID-19 public health emergency of international concern on May 5, 2023. This decision sparked debate, notably around the possibility of a surge in cases due to the SARS-CoV-2 mutations. To manage this transition, the Indonesian government enacted stringent controls on case numbers. This case series study provided an overview of COVID-19 case trends in Indonesia following the revocation of public health emergency of international concern status by the World Health Organization. Data were collected for 5 weeks after the statement (May 6–June 10, 2023) from the COVID-19 Task Force’s official online platform of the Indonesian Ministry of Health. The trends were monitored in daily confirmed, active, recovered, and death cases, and analyzed the data using Microsoft Excel and Stata 16. The findings indicated a positive trend for Indonesia, with decreased daily confirmed cases (89.42%) and active cases (44.16%). Recovered cases accounted for 97.47%, higher than the global average (96%). Unfortunately, the death rate (2.38%) exceeded the global statistic (1%). These results highlighted the need for sustained vigilance, enhancement of the 3T strategy (testing, tracing, and treatment), and wider vaccination coverage. It remains critical to uphold the 3M protocols—mask-wearing, physical distancing, and hand hygiene—to prevent a potential rebound in cases, even without the public health emergency of international concern status,as the situation transitions toward endemic COVID-19.